2015
DOI: 10.1177/2333721415582119
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Loneliness on Quality of Life and Patient Satisfaction Among Older, Sicker Adults

Abstract: Objective: This study estimated prevalence rates of loneliness, identified characteristics associated with loneliness, and estimated the impact of loneliness on quality of life (QOL) and patient satisfaction. Method: Surveys were mailed to 15,500 adults eligible for care management programs. Loneliness was measured using the University of California Los Angeles (UCLA) three-item scale, and QOL using Veteran’s RAND 12-item (VR-12) survey. Patient satisfaction was measured on a 10-point scale. Propensity weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
88
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 39 publications
15
88
1
2
Order By: Relevance
“…Although the IOM report focused on measures of social connection and isolation, loneliness was considered a subcomponent of these measures, and several different measures of loneliness have been used to establish its relevance to health and risk for mortality. Loneliness may be easily identified using the UCLA three‐item loneliness scale (Supplementary Table S1) . Efforts are underway to incorporate this loneliness screen into EHRs.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the IOM report focused on measures of social connection and isolation, loneliness was considered a subcomponent of these measures, and several different measures of loneliness have been used to establish its relevance to health and risk for mortality. Loneliness may be easily identified using the UCLA three‐item loneliness scale (Supplementary Table S1) . Efforts are underway to incorporate this loneliness screen into EHRs.…”
Section: Epidemiologymentioning
confidence: 99%
“…Loneliness may be easily identified using the UCLA three-item loneliness scale ( Supplementary Table S1). 26,31,36,46,[51][52][53][54] Efforts are underway to incorporate this loneliness screen into EHRs. For example, Caremore, United, and Cigna each have made efforts to screen for loneliness.…”
Section: What Is Socialmentioning
confidence: 99%
“…While loneliness can be described as the subjective negative feeling that one's social network is smaller and of poorer quality than desired, 1 size reflects one aspect of the social network that can also be characterized by its density, accessibility, and reciprocity. 3,4 From an economic perspective, loneliness is associated with increased health care utilization and hence expenditures. 2 Loneliness has a negative impact on those affected.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is linked to risk of an earlier death [1,7] depression [8], dementia [9] and poor self-rated health [10]. Many factors have been identified that increase the risk of social isolation among the elderly, including physical or mental decline, relationship factors and low income.…”
mentioning
confidence: 99%